Enhancing special needs literacy: insights from Indonesian inclusive schools - Kurniawan, Redite; Zulkarnain, Zulkarnain; Khoiriyah, Siti (Intelektual Pustaka Media Utama, 2026)
The study focuses on the inclusive school’s approach to literacy development for special needs students (SNS). The research aims to delve into the inclusive school’s methodologies concerning literacy development, particularly tailored to cater to the diverse needs of special education students. The study was conducted in 17 inclusive schools across 3 provinces in Indonesia, all of which have demonstrated remarkable progress in literacy development. This comprehensive investigation involved meticulously surveying these schools to gather insights into their practices and achievements. The findings of the study highlight several patterns in the approach to literacy development in inclusive schools. A comprehensive inclusive literacy development model is proposed, which emphasizes personalized planning, multimodal and experiential learning, differentiated instruction, recognition of achievements, and ongoing professional development. The study’s insights are relevant for educators, policymakers, and researchers interested in enhancing inclusive literacy practices for SNS in inclusive school settings schools. The practicality of the curriculum is seen from the aspect of good communication, cooperation, sufficient time, and the ease of understanding the material.